Analysis of stress and strain concentration around a centralized elliptical hole in a monodomain liquid crystal elastomer sheet - Jiang, Yuefeng; Li, Donghao; Chen, Yuzhen; Huo, Yongzhong (International journal of solids and structures, 2023)
•The strain and stress concentration behaviors of a monodomain LCE sheet with an elliptical hole subjected to uniaxial stretches are studied using finite element methods.•Liquid crystal elastomers exhibit severer stress and strain concentration than neoHookean, and such concentration is further aggravated with the sharpening of the elliptical hole.•The location of maximal strain deviates slightly from that of maximal stress when the applied stretches are small. The two locations merge together as the elliptical holes become sharper or the applied stretches become larger.•Director reorientations and resulting spontaneous strains around the hole edge are the main causes of these unusual stress and strain concentration behaviors. Liquid crystal elastomers (LCEs) are a kind of soft materials which couple the high elastic deformability with the unique properties of liquid crystals. Such combination endows notched LCEs unusual stress and strain concentration behaviors, which is preliminary discussed by us in the case of a large sheet with a centralized circular hole. Here we extend our study from circular holes to more generalized, elliptical holes. We investigate the stress and strain fields around a centralized elliptical hole in a LCE sheet subjected to uniaxial stretches by finite element methods. The effects of the shape factor, defined as the ratio of the minor-to-major axis of the ellipse, are mainly concerned. Compared with common elastomers like neoHookean, LCEs get higher stress and strain concentration factors (SCFs), and the location of maximal strain deviates slightly from that of maximal stress. With the decrease of the shape factor (a sharper ellipse) the SCFs of LCEs rise much severer than those of neoHookean, and the deviation is diminishing. In addition, as the stretch increases, the region near the root is getting close to an approximately uniaxial stress state, and the high strain region will extend non-monotonously along the hole edge, which differs from a monotonous extension of the high stress region. All the unusual behaviors of LCEs above are attributed to the spontaneous strain induced by director rotation. Attempts to correlate stress and strain concentration behaviors to the spontaneous strain are made in this article.